Nonprofit management 101 a complete and practical guide for leaders and professionals - Heyman, Darian Rodriguez 1974-; Brenner, Laila (Wiley, 2019)
"Emerging leaders, early career professionals and small to medium sized organizations need to grow to achieve impact. Many of those entering the nonprofit field today are passionate people driven to make change but often they don't know where to start when it comes to running or working within an effective organization. Many are familiar with and knowledgeable of their cause, but don't know how to achieve impact in the complicated and challenging environments nonprofits operate in. In the 7 years since the first edition has published, so much has changed with regards to the nonprofit industry including laws, regulations, social movements, etc.. This update with address all of that and much more. Written by a number of top authorities in the nonprofit field (Darian Rodriguez Heyman, Beth Kanter, Bruce Hopkins, Tori O'Neal McElrath, etc.) this book gives a HUGE amount of insight and wisdom gleaned from years of experience from some of the top names in the field"--Publisher.